Culinary tourists in the Spanish region of Extremadura, Spain - Tomás López-Guzmán; Elide Di-Clemente; José Manuel Hernández-Mogollón (Wine Economics and Policy)
Food and wine are considered to be part of the cultural identity of an area. In recent years, this identity has been getting stronger and creating possibilities for tourist destinations which, in turn, is supporting the economic development of certain regions. This paper presents a study into the relationship between wine, food and culture in the Spanish region of Extremadura. As part of this study, a survey of tourists dining in restaurants of the city of Cáceres was carried out. The main results of this study show that food and wine are closely linked to culture; cuisine and culture are the resources which tourists value most highly and desire most; and culinary tourists are distinguished by their high cultural and income levels, which make them an attractive market segment for tourist destinations.